Principles of teaching 2 - Arcilla-Serapio, Maria Perpetua (Quezon City, Philippines : Maxcor Publishing House Inc., 2016)
The field of education is the Philippines is encountering changes that brings new challenges for both teachers and students.
CHAPTER 1. Nature and structure of different subject areas in the elementary and secondary curriculum -- 2. Principles of teaching/Learning of the different subjects areas -- 3. Modern Methods of teaching -- 4. Problem-solving method -- 5. Collaborative Learning or group work method -- 6. Integrative method -- 7. Thematic Method -- 8. Cooperative Learning -- 9. Investigation-Oriented Activities (Inquiry-based Learning) -- 10. Metacognition -- 11. Constructivism -- 12. Multiple Intelligence -- 13. Learning style -- 14. Art of questioning -- 15. Writing Objectives -- 16. Lesson Planning -- 17. Instructional design -- 18. outcome-Based Education.
Includes bibliographical references.
Keywords: TEACHING PRINCIPLES